2019
DOI: 10.1038/s41535-019-0179-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and in-gap states of 3d transition metal atoms on superconducting Re

Abstract: Magnetic atoms on heavy-element superconducting substrates are potential building blocks for realizing topological superconductivity in one-and two-dimensional atomic arrays. Their localized magnetic moments induce so-called Yu-Shiba-Rusinov (YSR) states inside the energy gap of the substrate. In the dilute limit, where the electronic states of the array atoms are only weakly coupled, proximity of the YSR states to the Fermi energy is essential for the formation of topological superconductivity in the band of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 69 publications
4
34
1
Order By: Relevance
“…2g, h). These results let us conclude that the relatively weak Kondo coupling 23 of Mn compared to Fe prevents the development of a topologically superconducting phase via the YSR bands 4 . Notably, the energy of the YSR band is slightly decreased at the chain's ends, and thus somewhat approaches the Fermi level (see arrows in Fig.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…2g, h). These results let us conclude that the relatively weak Kondo coupling 23 of Mn compared to Fe prevents the development of a topologically superconducting phase via the YSR bands 4 . Notably, the energy of the YSR band is slightly decreased at the chain's ends, and thus somewhat approaches the Fermi level (see arrows in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…By depositing the three transition-metal elements onto the cold Re(0001) substrate and subsequent STM-tip induced manipulation (see "Methods"), we place single Fe and Co atoms on two different adsorption sites: the hollow site that continues the hexagonal close-packed (hcp) stacking of the substrate, and the hollow site that corresponds to the stacking of a face-centered cubic (fcc) crystal. For single Mn atoms, only the fcc site is accessible 23 . Due to increasing Kondo coupling with increasing d-state filling and a transition from out-of-plane to easy-plane magnetic anisotropy, the energy of the YSR states, which the five species induce in the energy gap of the superconducting substrate, varies systematically from Mn fcc over Fe fcc , Fe hcp , and Co fcc to Co hcp : the YSR states of Mn fcc are located close to the superconducting substrate's gap edge, the ones of Fe hcp close to the center of the gap, and the ones of Co fcc again at the gap edge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] The YSR states are very sensitive to the immediate environment of the impurity spin and give information on the role of the local environment on the exchange interaction J of an impurity spin with a superconductor. 3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin.…”
mentioning
confidence: 99%
“…3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin. The bound state results from the spin-dependent scattering of Bogoliubov quasiparticles on the impurity and is thus associ-ated with the longitudinal part of the exchange interaction, JS z s z , where s represents the spin-density of the substrate electrons at the impurity position.…”
mentioning
confidence: 99%